High frequency trading and end-of-day price dislocation - Michael Aitken; Douglas Cumming; Feng Zhan (Goethe University Frankfurt, Center for Financial Studies (CFS), 2013)
We show that the presence of high frequency trading (HFT) has significantly mitigated the frequency and severity of end-of-day price dislocation, counter to recent concerns expressed in the media. The effect of HFT is more pronounced on days when end of day price dislocation is more likely to be the result of market manipulation on days of option expiry dates and end of month. Moreover, the effect of HFT is more pronounced than the role of trading rules, surveillance, enforcement and legal conditions in curtailing the frequency and severity of end-ofday price dislocation. We show our findings are robust to different proxies of the start of HFT by trade size, cancellation of orders, and co-location.
urn:nbn:de:hebis:30:3-324935
Keywords: G12; G14; G18; K22; 330; High frequency trading; End-of-day Price dislocation; Manipulation; Trading Rules; Surveillance; Law and Finance